2022
DOI: 10.3390/ijms23169439
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PgCBF3 and PgCBF7 Transcription Factors from Pomegranate Enhances Freezing Tolerance in Arabidopsis under the Promoter Activity Positively Regulated by PgICE1

Abstract: Cold stress limits plant growth, development and yields, and the C-repeat binding factors (CBFs) function in the cold resistance in plants. However, how pomegranate CBF transcription factors respond to cold signal remains unclear. Considering the significantly up-regulated expression of PgCBF3 and PgCBF7 in cold-tolerant Punica granatum ‘Yudazi’ in comparison with cold-sensitive ‘Tunisia’ under 4 °C, the present study focused on the two CBF genes. PgCBF3 was localized in the nucleus, while PgCBF7 was localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In plants, β-amylase primarily catalyzes the hydrolysis of starch. The availability of extensive genomic data from various species has greatly facilitated the identification of Additionally, the expression of PgCBF7 (LOC116202526), a known transcription factor crucial for pomegranate's cold response [25,31], was also detected. Despite differences in cold stress tolerance, PgCBF7 was significantly upregulated under LT in both 'Tunisia' and 'Sanbai' cultivars (Figure 9D), confirming its pivotal role in regulating cold responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, β-amylase primarily catalyzes the hydrolysis of starch. The availability of extensive genomic data from various species has greatly facilitated the identification of Additionally, the expression of PgCBF7 (LOC116202526), a known transcription factor crucial for pomegranate's cold response [25,31], was also detected. Despite differences in cold stress tolerance, PgCBF7 was significantly upregulated under LT in both 'Tunisia' and 'Sanbai' cultivars (Figure 9D), confirming its pivotal role in regulating cold responses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the expression of PgCBF7 (LOC116202526), a known transcription factor crucial for pomegranate's cold response [25,31], was also detected. Despite differences in cold stress tolerance, PgCBF7 was significantly upregulated under LT in both 'Tunisia' and 'Sanbai' cultivars (Figure 9D), confirming its pivotal role in regulating cold responses.…”
Section: Pgcbf7 May Play a Role In Regulating Pgbam4 Expression For C...mentioning
confidence: 99%
See 1 more Smart Citation
“…JA, ethylene and ABA signalling pathways regulate the biosynthesis of many defensive compounds, such as terpenoids and phenolics (Divekar et al, 2022; Erb & Reymond, 2019; He et al, 2022; Wari et al, 2022). Moreover, a number of DREB/CBFs, including OsDREB1A, are known to promote plants' resistance to cold by increasing the content of amino acids and soluble sugars (Feng et al, 2019; Ito et al, 2006; Lata & Prasad, 2011; Wang et al, 2022), compounds that benefit BPH fitness (Chen et al, 2011; Huang et al, 2015; Liu et al, 2021). Which compounds are responsible for the decrease in the performance of BPH on irDREB lines should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most critical TFs functioning in the low-temperature signal transduction, C-repeat binding factors (CBFs) regulate the downstream gene expression, promote the synergy of multiple functional genes, and enhance the adaptability and resistance of plants ( Gilmour et al., 2000 ; Liu et al., 2022 ). It has been reported that overexpression of CBFs can stimulate the synthesis of soluble sugars (e.g., sucrose, raffinose, glucose and fructose) and improve the cold tolerance of pomegranate ( Wang et al., 2022 ). In this study, we identified three CBF genes (Prupe.4G242700, Prupe.5G090100 and Prupe.5G090000) were significantly upregulated in peach branches under cold stress ( Table S5 ).…”
Section: Discussionmentioning
confidence: 99%